GPA Tracking Report - Office of Assessment (Kansas State University. K-State First., 2014)
Cumulative End-of-Year GPAs for K-State First Students and Non-K-State First Students
Keywords: GPA; Enrollment; First-year seminars; Learning communities; Papers (document genres)